Investigating factors affecting unreasonable use of costly imaging services in general hospitals of Iran - Mehrak Pourmotahari; Soad Mahfoozpour; Shahram Tofighi; Shaghayegh Vahdat; Irvan Masoudi Asl (Tehran University of Medical Sciences, 2024)
Background and purpose: As health resources face increasing constraints, the use of medical imaging services has risen significantly. On average, diagnostic services account for approximately 10% of total healthcare expenditures, and this figure is steadily increasing. This study aims to identify the causes of irrational utilization of medical imaging services and propose corrective measures. Methods: This descriptive-survey research was conducted in two phases. In the first phase, a comprehensive literature review was performed using both international and national databases, covering the period from 1990 to November 2021. Relevant studies were identified using specific keywords. In the second phase, a semi-structured questionnaire was developed, and a series of in-depth interviews with experts and professionals were conducted. Data were analyzed using the six-step thematic approach by Braun and Clarke, utilizing MAXQDA software. Results: A total of 605 studies were initially identified, of which seven met the inclusion criteria after rigorous screening. In the second phase, 12 in-depth interviews were conducted, yielding 65 codes, which were organized into 12 themes. The identified themes included legal issues, conflict of interest, monitoring challenges, poor governance and stewardship, inappropriate policymaking and planning, financial incentives, inadequate service provision infrastructure, health culture, education and continuous training systems, financing and purchasing services, political factors, and inadequate insurance systems. Various strategies for controlling the inappropriate use of diagnostic and therapeutic services were proposed, including policy interventions, monitoring and evaluation, and training. Conclusion: The irrational use of healthcare services is a significant challenge in many countries. Key contributing factors include incomplete insurance coverage, out-of-pocket payments by patients, defensive medical practices, and gaps in knowledge. Addressing these issues requires targeted interventions and reforms.